Globalização, tecnologia e mídias: elementos constituintes do estar-junto juvenil na contemporaneidade - Sousa, Nádia Jane de (2010)
The theme related to youth and its gathering, pointing out another way to be together as a social enhancer, is discussed at this moment. For this reason, this study arose from a group of youngsters who practice street dance in the town of Cajazeiras, PB. Having as theoretical and methodological axis, Michel Maffesoli´s comprehensive sociology, the study aimed to identify and analyze the sociocultural and educational elements which constitute and which are constituents of these youngsters´ practice. The research, however, demonstrates the street dance as an educative experience, characterized as the way youngsters, involved in it, found to be together. Such experience, nevertheless, translates the dynamicity and plurality of a world in a constant social movement which is reflected in the daily routine of the groups while in interaction, constitutive of identities which are not rigid, but kaleidoscopic. In this sense, matters as global/local culture, youth culture, media, identity, recognition, tribalization and educability compose important axes for understanding the changes concerning the social experiences, especially among the youngsters, nowadays.